IRON STATUS: IS THERE A ROLE IN FEBRILE SEIZURES? - Waheed, Nadia; Butt, Muhammad Asghar (Journal of Ayub Medical College Abbottabad, 2012)
Background: Febrile seizure a common convulsion disorder in children, can lead to increased morbidity and mortality because of risk of aspiration and hypoxia during prolonged febrile seizures. There are many risk factors associated with febrile seizures and their recurrence. We conducted this study to see if there is a role of iron status in febrile seizures. Methods: This cross-sectional study was conducted in 323 children 6 months to 5 years of age admitted in department of Paediatric DHQ Hospital Faisalabad with fever and seizures from July 2009 to April 2011. Iron deficiency anaemia including haemoglobin concentration (Hb), Mean Corpuscular Volume (MCV), Mean Corpuscular Haemoglobin (MCH) and Plasma Ferritin were measured. Results: Febrile seizures were more common between ages 12 months to 36 months. Of 323 children with febrile seizures 17 (5.3%) were iron deficient. Mean Hb was 11.71±1.38 g/dL, mean MCV 78.40±3.29, mean MCH 27.11±3.28, and mean ferritin was 66.57±24.7. Conclusion: Iron deficiency anaemia was not common in patients with seizures. Iron status has no role in febrile seizures. Keywords: Iron deficiency anaemia, febrile seizures